Analytic Theology as Declarative Theology - Arcadi, James M. (TheoLogica, 2017)
Analytic theology seeks to utilize conceptual tools and resources from contemporary analytic philosophy for ends that are properly theological. As a theological methodology relatively new movement in the academic world, this novelty might render it illegitimate. However, I argue that there is much in the recent analytic theological literature that can find a methodological antecedent championed in the fourteenth century known as declarative theology. In distinction from deductive theology—which seeks to extend the conclusions of theology beyond the articles of faith—declarative theology strives to make arguments for the articles of faith. It does it not to provoke epistemic assent to the truth of the articles, but serves as a means of faith seeking understanding. In this paper, examples are drawn from recent analytic discussions to illustrate the manner that analytic theology has been, is, and can be an instance of declarative theology, and thus a legitimate theological enterprise for today.